IMPLEMENTATION OF VILLAGE INFORMATION SYSTEM IN INCREASING PUBLIC INFORMATION DISCLOSURE IN KENDALPECABEAN VILLAGE CANDI DISTRICT, SIDOARJO REGENCY - Putri, Cantika Alif; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the Implementation of Village Information System (SID) in improving Public Information Disclosure in Kendalpecabean Village, Candi District, Sidoarjo Regency. Method: This study uses a descriptive qualitative approach with data collection techniques through observation, interviews and documentation. Results: The results of the study show that SID contributes significantly in improving transparency, public services and efficiency of village administration. However, there are still several obstacles such as limited human resources who do not fully understand technology, and the preparation of standard operating procedures (SOPs) is not optimal. Policy implementation is analyzed using the theory of Erward III which includes indicators of communication, resources, disposition and bureaucratic structure. Novelty: The findings of the study show that although the infrastructure and commitment of the implementers have been supportive, training, the preparation of SOPs and efforts to increase public trust in SID still need to be improved. This research emphasizes the importance of strengthening capacity and support from local governments so that the implementation of SID is more optimal in village governance.